ORGANIC AGRICULTURE AS A PILLAR OF SUSTAINABLE FOOD SECURITY: AN ANALYSIS OF VARIOUS STUDIES - Imam Widodo; Ivonne Fitri Mariay; Veronica L. Tuhumena (ADISAM Publisher, 2025)
Organic farming plays an important role in supporting sustainable food security through improving soil fertility, conserving biodiversity, and reducing the use of synthetic chemicals. Studies indicate that this practice not only produces healthier food but also has the potential to improve farmers' economic welfare through job creation and higher selling prices. However, there are implementation challenges such as certification costs and the need for specialised knowledge. Support from the government and relevant institutions is needed to overcome these obstacles and maximise the benefits of organic farming for food security and a more sustainable environment.